Integration of Indian Psychological Traditions (Yoga, Meditation, and Mindfulness) into Modern Mental Health Practice: A Conceptual and Systematic Review - Sandhya Sood (International Journal of Education, Modern Management, Applied Science & Social Science, 2026)
The growing global burden of mental health disorders has highlighted the limitations of exclusively biomedical and symptom-focused treatment models, prompting renewed interest in holistic and culturally rooted approaches to psychological well-being. Indian psychological traditions—particularly yoga, meditation, and mindfulness—offer comprehensive frameworks that integrate cognitive, emotional, behavioral, and spiritual dimensions of mental health. Rooted in classical philosophical systems such as the Yoga Sutras, Buddhist contemplative practices, and Vedantic thought, these traditions conceptualize mental distress not merely as pathology but as imbalance in consciousness, lifestyle, and self-awareness. This paper aims to examine the relevance and integration of Indian psychological traditions within contemporary mental health practices through a secondary data–based conceptual and systematic review of existing literature. Drawing on interdisciplinary research from psychology, psychiatry, neuroscience, and integrative medicine, the study synthesizes empirical findings on the therapeutic effectiveness of yoga-based interventions, meditation techniques, and mindfulness-based clinical programs in reducing anxiety, depression, stress, and psychosomatic disorders. The analysis also explores theoretical convergences between Indian holistic psychology and modern approaches such as cognitive-behavioral therapy, positive psychology, and mind-body medicine. The review identifies increasing global institutional acceptance of contemplative practices, while also highlighting conceptual distortions, methodological limitations, and the need for culturally grounded integration models. The paper contributes by proposing a structured framework for integrating Indian psychological knowledge systems into modern mental health care, with implications for clinical practice, research, and mental health policy.